ДЕНДРИТНОКЛІТИННА ВАКЦИНА В ЛІКУВАННІ ГЛІОБЛАСТОМ ГОЛОВНОГО МОЗКУ - Главацький, О. Я.; Храновська, Н. М.; Горбач, О. І.; Хмельницький, Г. В.; Шуба, І. М.; Земскова, О. В. (Українські медичні вісті, 2023)
ДЕНДРИТНОКЛІТИННА ВАКЦИНА В ЛІКУВАННІ ГЛІОБЛАСТОМ ГОЛОВНОГО МОЗКУ